Relative Preference to Host Plants by a Polyphagous Insect, Spilarctia obliqua Walk. (Lepidoptera : Arctiidae) - Faisal, Mohammad; Ahmad, Mukhtar (Indian Forester, 2009)
Spilarctia obliqua, commonly known as 'Bihar hairy caterpillar', is a polyphagous pest of great economic value. Its sporadic presence has been recorded on variety of food plants of agriculture and forestry importance. Relative feeding preference of S. obliqua has been studied by providing measured leaves of its five main host plants including Brassica compestris, Paulownia fortunei, Populus deltoides, Tectona grandis and Toona ciliata to different larval instars. A single larva of S. obliqua during its total larval period has consumed 377.32 mg foliage of P. fortunei which is the maximum among the five host plants tested. It was followed by B. compestris (150.19 mg), P. deltoides (72.60 mg), T. grandis (60.00 mg) and T. ciliata (43.81 mg). Taking consumption of average leaf area as the criteria, maximum leaf area of 991.14 mm2 of P. fortunei was found consumed while that of T. ciliata was minimum (138.15mm2). Larva consumed 442.86 mm2 leaf area of B. compestris and 195.90mm2 and 176.71mm2 of P. deltoides and T. grandis respectively.